Effect of Shuddha Guggulu on Metabolic Syndrome - A Case Report (International Journal of Ayurveda and Pharma Research, 2022)
Metabolic syndrome is conglomeration of symptoms composed of impaired fasting glucose, abdominal obesity, hypertension and dyslipidemia. It is associated with cardio metabolic risk factors with increased risk of multiple chronic diseases, including cancer and cardiovascular disease because of the increased amount of visceral fat together with a chronic inflammatory state.Metabolic Syndrome is resulted by the causative factors which are Santarpanakaraka in nature leading to Medodushti, which in turn leads to Medoroga. The Santarpana karaka Nidanas include the food articles that are rich in Snigdhamsha, Madhura rasa, Guru and Pichchila gunas. By consuming the food rich in such qualities produces the Rasa dhatu which is excessively composed of the qualities like Ati Snehamsha and Madhuratara Guna which produces excess Medo dhatu and causes Sthoulya. Ama present in the Medodhatu leads to further Medo dushti and manifests Metabolic Syndrome.Shuddha Guggulu is potent Ama pachaka dravya and does Pachana of the circulating Atisnigdha Ama in the form of lipoproteins. And also Guggulu having Lekhaneeya Guna reduces deposition of Medo dhatu and prevents inflammatory process by its anti- inflammatory potential. Aim: To assess the effect of Shuddha Guggulu in Metabolic Syndrome, dyslipidaemia. Methodology: Oral administration of the preparation in the patient. Result: There was marked improvement in signs, symptoms and biochemical parameters after intervention. Conclusion: Shuddha Guggulu is significantly effective in reducing lipid levels and CRP